Model of Discovery learning in Science Learning: Bibliometric Analysis of the Current State of the art and Perspectives - Noor Izzati Pratiwi; Misbah Misbah; Sarah Miriam; Muhdi Harto; Nurlaela Muhammad (Universitas Lambung Mangkurat, 2022)
This study aims to evaluate the most relevant themes related to discovery learning through bibliometric analysis, with its input using the keyword